Maresin 1 Mitigates High Glucose-Induced Mouse Glomerular Mesangial Cell Injury by Inhibiting Inflammation and Fibrosis - Shi Tang; Chenlin Gao; Yang Long; Wei Huang; Jiao Chen; Fang Fan; Chunxia Jiang; Yong Xu (Hindawi Limited, 2017)
Background. Inflammation and fibrosis are the important pathophysiologic processes in diabetic nephropathy (DN). Maresin 1 is a potential anti-inflammatory lipid mediator, which has displayed powerful proresolving activities. Aim. We determine whether maresin 1 has protective effect on mouse glomerular mesangial cells (GMCs) induced by high glucose. Methods. We cultured GMCs stimulated by high glucose and categorized as follows: normal glucose group (5.6 mmol/L), high glucose group (30 mmol/L), mannitol group, maresin 1 intervention group (1, 10, and 100 nmol/L), maresin 1 and normal glucose group, and the N-acetylcysteine (NAC) intervention group (10 μmol/L NAC). After 24 h, the expression of ROS, NLRP3, caspase-1, procaspase-1, IL-1β, and pro-IL-1β was detected by western-blot, RT-PCR, and immunofluorescence. After 48 h, the expression of TGF-β1 and FN was detected by RT-PCR and ELISA. Results. Compared with normal glucose group, the expression of ROS, NLRP3, caspase-1, IL-1β, TGF-β1, and FN increased in high glucose group (P<0.05), but it decreased after the treatment of maresin 1 in different concentrations. On the contrary, the expression of procaspase-1 and pro-IL-1β protein was restrained by high glucose and enhanced by maresin 1 in a dose-dependent manner (P<0.05). Conclusion. Maresin 1 can inhibit NLRP3 inflammasome, TGF-β1, and FN in GMCs; it may have protective effect on DN by mitigating the inflammation and early fibrosis.